ENTREPRENEURIAL ACTIVITY IN THE CONTEXT OF INNOVATIVE GROWTH AND SOCIO-ECONOMIC DEVELOPMENT OF TERRITORIES - RUDACHENKO, Olha; KONENKO, Vitalina; MEDVEDEV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the role of entrepreneurial activity as a key factor in ensuring innovative growth and sustainable socio-economic development of territories in the current conditions of global transformations and economic instability. Particular attention is paid to a comprehensive analysis of the relationship between the development of small and medium-sized enterprises, the formation of innovative ecosystems and the spatial heterogeneity of regional development in Ukraine, which is determined by different levels of innovation activity and availability of resources in the regions. The factors that promote or hinder the development of the innovation environment, in particular the role of state support, the availability of infrastructure for the introduction of new technologies, as well as the development of human capital capable of ensuring innovation activity and competitiveness, are analyzed. The mechanisms for creating a favorable innovation environment are explored, including support for innovative projects through financial, organizational, and educational tools, as well as the active introduction of digital technologies that play a crucial role in improving the efficiency of business processes. The author substantiates the need to move from traditional management forms to a strategic and institutional approach to managing innovation processes, considering the challenges of the sixth technological order. The author proposes an approach that effectively synchronizes the activities of entrepreneurial structures with state and regional development policies, creating conditions for harmonious socio-economic development of territories, considering their unique characteristics and needs. The study results are of practical importance and can serve as a reliable basis for the formation of effective state and local strategies and policies aimed at stimulating innovative entrepreneurship, strengthening the creative potential of the regions of Ukraine and ensuring their competitiveness at the national and international levels.